An Amish mother's secret past - Brown, Jo Ann (Love inspired., 2020)
Widow Rachel Yoder has a secret: she<U+2019>s a military veteran trying to give her children a new life among the Amish. Though she<U+2019>s drawn to bachelor Isaac Kauffman, she knows she can<U+2019>t tell him the truth<U+2014>or give him her heart. With her forbidden past, Rachel can never be the perfect Plain wife he<U+2019>s looking for<U+2026>